Optimalisasi Manajemen Pembiayaan Pendidikan Untuk Meningkatkan Fasilitas Belajar Di Mts Al-Khairiyah Pengoreng Kecamatan Puloampel Kabupaten Serang Provinsi Banten - Ofandi Ofandi; Muslihun Muslihun (CV. ITTC INDONESIA, 2025)
This study aims to analyze the management of learning facilities and educational financing at MTS Al-Khairiyah Pengoreng and the impact of stakeholder involvement on both aspects. This study uses a qualitative approach with data collection techniques through interviews, observation, and documentation. The data obtained are analyzed using coding, categorization, thematic analysis, narrative analysis, and triangulation techniques to ensure the validity and reliability of the research results. The results of the study indicate that 1) The management of facilities and financing in this school still faces several gaps compared to ideal standards. Stakeholder involvement has a positive contribution, but there is a need for increased coordination and more effective allocation of funds. 2) The researcher found that stakeholder involvement plays a significant role in improving facilities and enhancing the quality of education. Active and coordinated involvement has a positive impact on facility management and support for the teaching and learning process, however, inconsistent involvement can hinder the achievement of optimal results. 3) Theoretical implications of this study include the development of theories on the management of educational facilities, educational financing, and educational quality by emphasizing the important role of stakeholder involvement. Practical implications include improving facility management strategies, optimizing educational financing, and developing more effective stakeholder involvement mechanisms.